Проблеми формування системи контролінгу міжнародної інноваційної діяльності підприємств - Одрехівський, М. В.; Пшик-Ковальська, О. О.; Odrekhivsky, M. V.; Pshyk-Kovalska, O. O. (Видавництво Львівської політехніки, 2005)
У статті сформовано структуру системи управління міжнародною інноваційною діяльністю підприємств, у якій контролінг міжнародної інноваційної діяльності підприємств реалізовується засобами господарського обліку, аналізу, контролю та аудиту. Ідентифіковано елементи системи контролінгу міжнародної інноваційної діяльності підприємств, а саме: організаційні, юридичні, функціональні, техніко-технологічні та фінансові елементи, елементи міжнародної співпраці та кадрової політики.

The article forms the structure of the management system of international innovation activities of enterprises, in which the controlling of international innovation activities of enterprises is implemented by means of economic accounting, analysis, control and audit. The elements of the control system of international innovation activity of enterprises are determined, namely: organizational and legal, functional, technical-technological and financial elements, elements of international cooperation and personnel policy. The essence and significance of economic, technical-economic, managerial, economic-static, factorial, marginal, stochastic analysis in the conditions of formation of the system of control of international innovative activity of enterprises are highlighted. According to the results of the study it was found that the formation of a system of controlling the international innovation of enterprises should be carried out by combining organizational, structural and functional components of the enterprise involved in the international process of creating and applying scientific knowledge and technologies that determine legal, economic, organizational and social conditions of the international innovation process in the conditions of the enterprise. It is substantiated that the functioning of the system of international innovation of enterprises is impossible without prompt, reliable and relevant information, its adequate analytical processing, as controlling the innovation of the enterprise plays an important role in the functioning of enterprises, ensures effective interaction of their structural units and responds to changes in the internal and external environment, based on data from accounting, control, audit and analysis. It is proved that the construction of the system of controlling the international innovation activity of enterprises allows to solve the problems of management of the international innovation activity of enterprises.
Problems of formation the controlling system of international innovative activity of enterprises
Keywords: контролінг; система контролінгу; інноваційне підприємство; інноваційна діяльність підприємств; міжнародна інноваційна діяльність підприємств; controlling; controlling system; innovative enterprise; innovative activity of enterprises; international innovative activity of enterprises; 339.9